Neurologic complications of kidney transplantation - Shoskes, Aaron (Transl Androl Urol, 2019)
Renal transplant is the most common organ transplant in the United States, and the frequency of kidney transplants continues to rise as transplant offers improved survival and quality of life compared to dialysis. However, complications are not uncommon and patients frequently encounter issues requiring hospitalization, especially in the first year postoperatively. Complications that arise are typically related to surgical complications, immunosuppressive medications, or infection due to immunosuppression. Neurological complications are fairly common post-operatively, and are associated with increased morbidity and mortality in this population. This review discusses the most common etiologies of neurological complications after kidney transplant, including infection, malignancy, medication related, acute neuropathy, and other neurological pathology.